Mutant CFTR Drives TWIST1 mediated epithelial-mesenchymal transition - Quaresma, Margarida C; Pankonien, Ines; Clarke, Luka A; Sousa, Luís S; Silva, Iris A L; Railean, Violeta; Doušová, Tereza; Fuxe, Jonas; Amaral, Margarida D (Cell death & disease, 2020)
Cystic fibrosis (CF) is a monogenetic disease resulting from mutations in the Cystic Fibrosis Transmembrane conductance Regulator (CFTR) gene encoding an anion channel. Recent evidence indicates that CFTR plays a role in other cellular processes, namely in development, cellular differentiation and wound healing. Accordingly, CFTR has been proposed to function as a tumour suppressor in a wide range of cancers. Along these lines, CF was recently suggested to be associated with epithelial-mesenchymal transition (EMT), a latent developmental process, which can be re-activated in fibrosis and cancer. However, it is unknown whether EMT is indeed active in CF and if EMT is triggered by dysfunctional CFTR itself or a consequence of secondary complications of CF. In this study, we investigated the occurrence of EMT in airways native tissue, primary cells and cell lines expressing mutant CFTR through the expression of epithelial and mesenchymal markers as well as EMT-associated transcription factors. Transepithelial electrical resistance, proliferation and regeneration rates, and cell resistance to TGF-β1induced EMT were also measured. CF tissues/cells expressing mutant CFTR displayed several signs of active EMT, namely: destructured epithelial proteins, defective cell junctions, increased levels of mesenchymal markers and EMT-associated transcription factors, hyper-proliferation and impaired wound healing. Importantly, we found evidence that the mutant CFTR triggered EMT was mediated by EMT-associated transcription factor TWIST1. Further, our data show that CF cells are over-sensitive to EMT but the CF EMT phenotype can be reversed by CFTR modulator drugs. Altogether, these results identify for the first time that EMT is intrinsically triggered by the absence of functional CFTR through a TWIST1 dependent mechanism and indicate that CFTR plays a direct role in EMT protection. This mechanistic link is a plausible explanation for the high incidence of fibrosis and cancer in CF, as well as for the role of CFTR as tumour suppressor protein.
Keywords: Nuclear Proteins; Cells, Cultured; kultivované buňky; jaderné proteiny; Oncogenes; Cystic Fibrosis Transmembrane Conductance Regulator; Twist-Related Protein 1; protein CFTR; HEK293 buňky; Humans; Cystic Fibrosis; HEK293 Cells; transkripční faktor Twist; epitelo-mezenchymální tranzice; onkogeny; lidé; cystická fibróza; Epithelial-Mesenchymal Transition